Análise da liquidez da Cooperativa de Crédito ABC no Rio Grande do Sul no período de 2010 a 2015 - Munchen, Maira Sabrina (Universidade do Vale do Rio dos Sinos, 2016)
This paper presents an analysis of ABC Credit Cooperative liquidity situation in the state of Rio Grande do Sul, in relation to the South Central, from 2010 to 2015. The indicators used in the study were from the liquidity group, of the PEARLS system. To assess the situation, descriptive statistics were used, based on financial statement data. They were short term data, since the liquidity risk is increased in shorter periods. In general, indicators reported that the Cooperative and Central are liquid and have an efficient risk management, this being necessary due to the financial market volatility.
Keywords: Cooperativa de crédito; Liquidez; Indicadores de liquidez; Risco; Gestão de riscos; Credit cooperative; Liquidity; Liquidity indicators; Risk; Risk management